2015
DOI: 10.1007/s11060-015-2012-x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone alone and in combination with desipramine, phenytoin, valproic acid or levetiracetam interferes with 5-ALA-mediated PpIX production and cellular retention in glioblastoma cells

Abstract: Extent of resection of glioblastoma (GBM) correlates with overall survival. Fluorescence-guided resection (FGR) using 5-aminolevulinic acid (5-ALA) can improve the extent of resection. Unfortunately not all patients given 5-ALA accumulate sufficient quantities of protoporphyrin IX (PpIX) for successful FGR. In this study, we investigated the effects of dexamethasone, desipramine, phenytoin, valproic acid, and levetiracetam on the production and accumulation of PpIX in U87MG cells. All of these drugs, except le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
0
20
1
1
Order By: Relevance
“…A recent in vitro study of glioblastoma cells demonstrated that corticosteroids result in a significantly decreased 5-ALA-induced PpIX production by tumor cells. 13 Additionally, we hypothesized that immunosuppression might alter the presence of fluorescence in lymphomas. Thus, we also investigated the influence of prior treatment with corticosteroids or immunosuppression on fluorescence.…”
Section: Influence Of Corticosteroids and Immunosuppression On 5-ala mentioning
confidence: 99%
“…A recent in vitro study of glioblastoma cells demonstrated that corticosteroids result in a significantly decreased 5-ALA-induced PpIX production by tumor cells. 13 Additionally, we hypothesized that immunosuppression might alter the presence of fluorescence in lymphomas. Thus, we also investigated the influence of prior treatment with corticosteroids or immunosuppression on fluorescence.…”
Section: Influence Of Corticosteroids and Immunosuppression On 5-ala mentioning
confidence: 99%
“…J. Lawrence и соавт. [38] показали, что дексаметазон (как сам по себе, так и в сочетании с фенитоином и вальпроатами) снижает накопление ПП IX в клетках культуры глиомы. Это послужило основанием для изучения влияния противосудорожных препаратов на флуоресцирующий эффект в нашей когорте пациентов с менингиомами.…”
Section: рис 6 пациентка б (клиническое наблюдение №4)unclassified
“…Dexamethasone, desipramine, levetiracetam, phenytoin, and valproic acid are drugs that tend to diminish GB fluorescence after 5-ALA so might be best avoided during 5-ALA PDT and CAALA [55,56]. Also potential generators of increased nitric oxide tend to antagonize 5-ALA [57] and so should be avoided.…”
Section: Cautions and Discussionmentioning
confidence: 99%